Application of the Islamic Market Concept in the Era of the Prophet Zaim Saidi’s Perspective - Yayuli, Yayuli; Hakim, Lukmanul; Isnaini, Anif Nur; Jannah, Nisa’ Zahrotul (Journal of Islamic Economics and Social Science (JIESS), 2022)
In the city of Surakarta there is a market that has a different system from the general market. The market is named "Muamalah Market". Established in 2009, this market is slightly different from the market in general because in practice it applies shari'ah elements. Researchers are interested in conducting research related to the mechanism for applying the concept of the Islamic market by using several indicators; Islamic market sunnah, the concept of hisbah, and price regulation. This research is a descriptive qualitative research using the interview method to obtain primary data sources, supported by scientific articles related to the Islamic market. Based on the research results, there are three main points that become the focus of the research, namely: the application of Islamic market indicators or sunnah, the concept of Hisbah or market supervision, and prohibition of price intervention. Based on the results of the analysis above, it can be concluded that the Surakarta Muamalah Market has implemented the three main research points well. Islamic Market indicators, namely: a market similar to a mosque, no private ownership, no tax and rent fees, no claim/booking of a place, no barriers or shops in the market, have been implemented well in Muamalah Market Surakarta. The Surakarta Muamalah Market Coordinator, apart from being the market chairman, also serves as al-muhtasib or market supervisor. In addition, there is no policy of intervention in the price of goods in the Surakarta Muamalah Market. The price of the goods is set based on the agreement between the buyer and seller.